WACANA BAHASA DAN KEKUASAAN DI INDONESIA (DARI PEMILU HINGGA KASUS BANK CENTURY) - Ahmad Nurcholis (Jurnal Bahasa Lingua Scientia, 2010)
There is a view that male and female speak language contradictively. Female is prone to use cooperative speech act, but male is prone to use the competitive one. The use of language which is gender-base discriminated turns to significantly contribute to the marginalization of women. English which seems to be ’innocent’ in this case, as a matter of fact, does not only reflect such ’gender bias’ but also immortalize that ’bias’. It turns out that language has ’certain hidden agenda’, that is discriminating the male and female. The existance of such gender bias can be traced from the sexist expression found such as (1) assymmetry, (2) mark and non mark expression, (3) derogative semantic, and (4) sexism in discourse. There are three theories which can be used to analyze such phenomena, they are domination theory, discrimination theory, and gender analysis theory.